Implementation of Digital Village by Creating Content for a Website as an Information Center in Banyumanik Village, Semanu, Gunung Kidul - Nastain, M.; Wulandari, Margaretha; Fariha, Naela Faza; Bintara, Chandra Satya; , Mutiara; Lestari, Feni Indah; Sari, Nur Mala Pusphita (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2024)
The activity method is divided into several stages, namely the coordination and preparation stage, the science and technology implementation stage, and the evaluation and monitoring stage. The activities carried out include training and management of supporting content, village profiling through shooting, audio recording, and video editing. The result of this service activity is the creation of content for the village website as an information center for village programs, village activities, assistance information from the regional or central government, and other information. In addition, a digital village profile is also created that can provide initial information about Banyumanik village. This activity aims to provide benefits for partners in disseminating village information in the future and can be an inspiration for other communities in developing communication media and village information through visual content.